2016
DOI: 10.1007/s12039-016-1184-z
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Metal Complexes for Mimic of SOD

Abstract: Superoxide anion radical (O •− 2) is a noxious reactive oxygen species (ROS). Transition metal ion complexes have been generally used as antioxidants to eliminate ROS. In this work, a neoteric watersoluble biopolymer metal complex (BSA-M) was prepared by conjugating the soluble biopolymer bovine serum albumin (BSA) with three transition metal ions (M, M=Cu, Co, Mn). The binding mode and ratio of metal ions bound to albumin were investigated. The BSA-M complexes were characterized by UV-Vis, circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
5
1
1
Order By: Relevance
“…The results indicated that the mount of metal ions (Cu II ) had important effect for anti-O Table 6 and Figure 10. Compared with the literature [31], of which EC 50 and degree of simulation, respectively, were 0.038 ± 0.003 mol/L and 107%; here EC 50 of prepared FK-GlyCu 60 was far below it and the degree of simulation was much bigger than it. The values, respectively, were up to 0.0045 ± 0.0012 mol/L and 911.1%.…”
Section: Ocontrasting
confidence: 73%
“…The results indicated that the mount of metal ions (Cu II ) had important effect for anti-O Table 6 and Figure 10. Compared with the literature [31], of which EC 50 and degree of simulation, respectively, were 0.038 ± 0.003 mol/L and 107%; here EC 50 of prepared FK-GlyCu 60 was far below it and the degree of simulation was much bigger than it. The values, respectively, were up to 0.0045 ± 0.0012 mol/L and 911.1%.…”
Section: Ocontrasting
confidence: 73%
“…Alkaline DMSO, a source of superoxide radical (O -2 ) and nitrobluetetrazolium (NBT) as a scavenger (O -2 ) were used to test in vitro SOD activity [44]. In general, a solution containing 2.1 mL of 0.2 M potassium phosphate buffer (pH 8.6) and 1 mL of 56 mM NBT was applied to the 400 mL sample to be analyzed.…”
Section: Sod Activitymentioning
confidence: 99%
“…Penentuan nilai IC 50 , yang merupakan aktivitas penangkal radikal superoksida dari sampel kompleks, didapatkan dengan menarik garis dari inhibisi 50% pada plot kurva antara persen inhibisi dan konsentrasi kompleks (Deawati et al 2017;Yan et al 2016).…”
Section: Persamaanunclassified